Tour Consumer Well-Being in Tourism Destination: A Case of the Lake Toba - Redha Widarsyah; Eka Ardianto; Albert Hasudungan (Budapest International Research and Critics University, 2022)
This study focuses on identifying the underlying well-being dimensionalities that exist in a tourism destination. Researchers conduct qualitative content analysis of digital platform of Lake Toba as a tourism destination. The methodology uses content analysis of secondary sources. The stages consist of condensation, coding, categorizing, and patterning the theme. By utilizing content analysis methodology, the study was able to identify seven dimensions of tour consumer well-being: 1) Biopsychological; 2) Cultural Identity; 3) Social Connectedness; 4) Spiritual Attunement; 5) Social Enterprising; 6) Inspirational Mindfulness; and 7) Environmental Altruism well-being. This research finds that Lake Toba as tourist destination activates reciprocal tour consumers in related to 7 well-being dimensions. Lake Toba as tourist destination embraces consumer tour to appraise the indigenous home and their collective enterprises.